Current situation and future development of transitional care in China (国内延续性护理发展现状) - HAN Yuan (韩媛); LIU Qin (刘琴); WANG Shuaiying (王帅颖) (Association of Integrative Nursing, 2021)
The transitional care is mainly used in the care of chronic diseases management, but in recent years, transitional care has also been extended to postoperative surgery, PICC tube placement, puerperium care and other aspects. There is no specific requirement for nursing staff, and most of them have not received professional training. Transitional care in China is rapidly popularizing and developing, but there are also problems that cannot be ignored in the development process. When the hospital vigorously promotes transitional care, it should focus on solving the existing problems in order to better implement transitional care, and then provide better medical care services for the current situation of China's aging population. (延续性护理主要运用于慢性疾病护理, 近年来在外科术后、PICC置管后、产褥期等方面应用广泛。国内延续性护理对护理人员尚未有明确要求, 大多未经过专业培训, 多为临床各科室护士担任。虽然国内延续性护理正在快速普及和发展, 但发展过程中也存在不可忽视的问题。医院在大力推行延续性护理时, 要着重解决目前存在的问题, 以便更好地实施延续性护理, 进而为国内人口老龄化的现状提供更好的医疗护理服务。)